Functional Analysis of Cellulose Synthase CesA4 and CesA6 Genes in Switchgrass (Panicum virgatum) by Overexpression and RNAi-Mediated Gene Silencing - Mazarei, Mitra; Baxter, Holly L.; Li, Mi; Biswal, Ajaya K.; Kim, Keonhee; Meng, Xianzhi; Pu, Yunqiao; Wuddineh, Wegi A.; Zhang, Ji-Yi; Turner, Geoffrey B.; Sykes, Robert W.; Davis, Mark F.; et al. (Frontiers in Plant Science, 2018)
Switchgrass (Panicum virgatum L.) is a leading lignocellulosic bioenergy feedstock. Cellulose is a major component of the plant cell walls and the primary substrate for saccharification. Accessibility of cellulose to enzymatic breakdown into fermentable sugars is limited by the presence of lignin in the plant cell wall. In this study, putatively novel switchgrass secondary cell wall cellulose synthase PvCesA4 and primary cell wall PvCesA6 genes were identified and their functional role in cellulose synthesis and cell wall composition was examined by overexpression and knockdown of the individual genes in switchgrass. The endogenous expression of PvCesA4 and PvCesA6 genes varied among including roots, leaves, stem, and reproductive tissues. Increasing or decreasing PvCesA4 and PvCesA6 expression to extreme levels in the transgenic lines resulted in decreased biomass production. PvCesA6-overexpressing lines had reduced lignin content and syringyl/guaiacyl lignin monomer ratio accompanied by increased sugar release efficiency, suggesting an impact of PvCesA6 expression levels on lignin biosynthesis. Cellulose content and cellulose crystallinity were decreased, while xylan content was increased in PvCesA4 and PvCesA6 overexpression or knockdown lines. The increase in xylan content suggests that the amount of non-cellulosic cell wall polysaccharide was modified in these plants., possibly as a compensation response to the decreased cellulose content; the result would be maintenance of cell wall integrity. The results suggest an interconnection between the cellular machinery controlling cellulose and xylan biosynthesis. Taken together, the results show that the manipulation of the cellulose synthase genes alters the cell wall composition and availability of cellulose as a bioprocessing substrate. Understanding the enzymes responsible for the synthesis and regulation of cellulose synthesis is key to engineering biofuel crops for cellulose production and more efficient extraction of glucose from cellulose.